Implementation of a realistic mathematics learning approach (PMR) and analytical thinking: The impact on students' understanding of mathematical concepts in Indonesia - Supriadi, Nanang; Putra, Rizki Wahyu Yunian; Fitriani, Fitriani (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Understanding of concepts is a fundamental ability to learn mathematics in a more meaningful way. Understanding concepts is one of the goals to be achieved in learning mathematics. This study aims to determine the impact of a realistic mathematics learning approach (PMR) and analytical thinking on students' understanding of mathematical concepts. This experimental research uses a posttest-only control design. The population in this study included students XI in Kasui sub-district, Way Kanan district, Lampung, Determination of the sample using cluster random sampling technique. The research sample was 72 students (36 in the experimental class and 36 in the control class). Hypothesis testing using ancova test. Based on the research results, it can be concluded that the realistic mathematics learning approach (PMR) has an influence on students' understanding of mathematical concepts by controlling analytical thinking, analytical thinking has an influence on students' understanding of mathematical concepts, and there is a simultaneous influence between the PMR approach and analytical thinking on understanding mathematical concepts student.